2011
DOI: 10.1002/app.34170
|View full text |Cite
|
Sign up to set email alerts
|

Chemorheology and thermomechanical characteristics of benzoxazine‐urethane copolymers

Abstract: In this research, processability and some important thermomechanical properties of polybenzoxazine (BA-a) modified with a highly flexible urethane elastomer (PU) are discussed. This copolymer has been reported to show synergy in its glass transition temperature and some mechanical properties thus provides a fascinating group of high temperature polymers with enhanced flexibility. The results reveal that a processing window of the BA-a/PU mixtures is widened with the increasing urethane prepolymer fraction, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
6
26
0
Order By: Relevance
“…It was found that raising the processing temperature increases the rate of crosslinking of the BA-a/ATBN mixture. Consequently, at higher temperature, the mixture reached its gel point more quickly and the gel time was shorter as similarly observed in BA-a/epoxy mixtures ( Ref 13,15). Furthermore, Fig.…”
Section: Network Formation Between Ba-a Monomer and Atbnsupporting
confidence: 73%
See 1 more Smart Citation
“…It was found that raising the processing temperature increases the rate of crosslinking of the BA-a/ATBN mixture. Consequently, at higher temperature, the mixture reached its gel point more quickly and the gel time was shorter as similarly observed in BA-a/epoxy mixtures ( Ref 13,15). Furthermore, Fig.…”
Section: Network Formation Between Ba-a Monomer and Atbnsupporting
confidence: 73%
“…Moreover, an ability of benzoxazine resins to blend with various other resins or polymers results in new resins with a broad range of applications ( Ref 5,10,11). For example, blending between benzoxazine resins and epoxy resins, polyurethanes, and dianhydrides (Ref [12][13][14][15][16] was considered to be a potentially effective measure to enhance thermal or mechanical properties as well as flammability of the polymers. Furthermore, thermosetting copolymers based on benzoxazine resins and rubbers such as amine-terminated acrylonitrile-butadiene (ATBN) and epoxyterminated liquid nitrile rubber (ETBN) have been reported to provide various useful characteristics ( Ref 17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polybenzoxazine provides some characteristics such as excellent dimension stability, high heat resistance, flame retardance and low moisture absorption as well as good dielectric properties in which cannot be found in traditional phenolic resins [6,7]. Alloying of polybenzoxazine with various other resins or polymers has been reported to economically provide a novel class of resin systems with superior performance [1,4,[8][9][10][11][12][13][14][15]. However, the major shortcoming of polybenzoxazine is its relatively high rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various efforts have been done to toughen polybenzoxazine such as by easily blending with more flexible monomers or polymers e.g. flexible epoxy resins [9,12], urethane elastomers [8,13], polyimides [14,15] or dianhydrides [16,17]. In recent reports, thermal and thermo-oxidative stabilities of polybenzoxazines have been substantially improved by alloying techniques [8,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation